Penguatan BUMDes melalui Diseminasi Teknologi Eco-enzyme dan Pupuk Organik untuk Mendukung Perencanaan TPS3R di Desa Tegalweru, Kabupaten Malang, Indonesia - Tunggul Sutanhaji, Alexander; Susilo, Adi; Hardoko, Hardoko; Sugianto Prabowo Rahardjo, Seto; Khotimah, Mujaroh; Setyono, Langgeng; Fiaqi Hamada, Ichi; Prayogo, Wisnu (Jurnal Pengabdian Masyarakat, 2026)
This community service program was conducted in Tegalweru Village, Dau Subdistrict, Malang Regency, in response to suboptimal waste management issues, particularly the high volume of domestic and agricultural organic waste which reached 56.43%. The objective of this program was to strengthen the institutional capacity of the Village-Owned Enterprise (BUMDes) Dewandaru and the local community through training on making eco-friendly products based on organic waste, namely eco-enzymes and organic fertilizer (compost). This program utilized the Participatory Action Research (PAR) method, involving 18 participants consisting of BUMDes Tegalweru members and a group of citrus farmers. The program evaluation was carried out using pre-test and post-test instruments, as well as surveys on participant satisfaction and participation interest. The evaluation results showed a significant increase in participants' understanding and technical skills by up to 90% regarding the 3R (Reduce, Reuse, Recycle) concept and organic waste processing. Furthermore, the majority of respondents expressed a high interest in independently implementing the training outcomes. As a concrete step to support program sustainability, the community service team donated an integrated waste shredder machine, technical training modules, and developed an initial technical concept for the construction of a Reduce, Reuse, Recycle Waste Management Site (TPS3R) accompanied by a planning layout document. This program is considered effective in strengthening local capacity and encouraging the creation of a community-based integrated waste management system initiative in the village.